2019
DOI: 10.1186/s12902-019-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

The pubertal development mode of Chinese girls with turner syndrome undergoing hormone replacement therapy

Abstract: Background Further knowledge about the pubertal development mode of girls with Turner syndrome (TS) who have undergone hormone replacement therapy (HRT) is beneficial to the proposal of an optimal HRT regimen. This study examined the pubertal development mode of girls with TS who underwent HRT and evaluated the characteristics of optimal sex induction therapy in girls with TS. Method We conducted a retrospective, longitudinal study over the past two decades at The First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…About one-third of girls with TS have spontaneous menstruation, usually in patients with a mosaic karyotype ( 22 ). Most patients with TS will need HRT to induce puberty and for maintaining female secondary sex characteristics, attaining peak bone mass and normalizing uterine growth ( 1 , 23 ). Studies have shown that having pubertal development at the right age has a positive effect on the psychological well-being of girls with TS ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of girls with TS have spontaneous menstruation, usually in patients with a mosaic karyotype ( 22 ). Most patients with TS will need HRT to induce puberty and for maintaining female secondary sex characteristics, attaining peak bone mass and normalizing uterine growth ( 1 , 23 ). Studies have shown that having pubertal development at the right age has a positive effect on the psychological well-being of girls with TS ( 16 ).…”
Section: Discussionmentioning
confidence: 99%